ANALYSIS OF RUPIAH STABILITY DURING THE COVID-19 PANDEMIC - Damanik, Henni Julianta; Annisa Ilmi Faried; Wahyu Indah Sari (PT. Arsil Reka Engineering, 2024)
The purpose of this study was to see the differences before and during the pandemic on the variables of Exchange Rate, Inflation, Interest Rates and the Money Supply. The method used is the Differential Test method. The results of this study show that there are no significant differences between the Exchange Rate, Inflation and Interest Rate variables before and during the Covid-19 pandemic in Indonesia. Then in the Variable Amount of Money Supply there are significant differences before and during the Covid-19 pandemic in Indonesia. Thus it can be seen that there is one variable that has a significant difference and three variables that have no significant difference before and during Covid-19. Therefore, in maintaining the stability of the value of the rupiah during the pandemic, the Central Bank must be more careful in maintaining the Money Supply. Where the Money Supply itself has a significant influence both before the pandemic and during the pandemic. If the Money Supply increases, Inflation will also increase, this has an impact on the stability of the Indonesian Rupiah Exchange Rate.